A Produção Intelectual Brasileira em Responsabilidade Social Empresarial – RSE sob a Ótica da Bibliometria - Sérgio Luiz do Amaral Moretti; Milton de Abreu Campanario (RAC: Revista de Administração Contemporânea, 2009)
This article develops the selection and analysis of the EnANPAD academic publications between 1997 and 2007. This source of information was object of rigorous and in depth research, including both the profile of the authors, the articles and the quotations. 216 articles were classified with 9,523 corresponding quotations. The quantitative analysis of the quotations aims to describe their characteristics and to test the applicability of the Lotka Law – LL, one to the bibliometric fundamentals, which states that the number of authors making n contributions is about 1 / n2 of those making one contribution. In mature scientific fields, it is expected that few scientists publish more and many publish a less, but under a certain distribution. It was possible to verify that the LL does not apply to the CSR, as it is tested against the quotations used. This means that the field is not mature, in scientific terms. It was also shown that the quotations of one year are not utilized in the following research year. Evidence shows the most frequent quotations are those of administration handbooks and famous authors not necessarily related to CSR. The area is dominated by the reproduction of the same ideas, strengthening the thesis of zone of intellectual comfort.